(untitled) (REMUNOM, 2025)
Guava contains phenolic compounds with antioxidant, anti-inflammatory, and antimicrobial properties that may benefit the digestive and immune health of piglets. This study investigated the effect of guava residue flour on the intestinal microbiota of post-weaning piglets, with diets containing guava flour and amoxicillin. Eleven treatments were evaluated in 33 piglets, incorporating dehydrated guava residue into the diets, and microbiological analysis of fecal samples was performed to count fecal coliforms and Lactobacillus spp. The results showed that tannins can benefit intestinal health, but their efficacy depends on dosage and interaction with antibiotics. High doses of antibiotics may cause dysbiosis and antibiotic resistance, while moderate doses of tannins may protect lactobacilli and promote a balanced intestinal environment. The combination of tannins and antibiotics was effective in reducing fecal coliforms, but prolonged antibiotic use may lead to bacterial resistance. The study highlights that tannins alone can be a sustainable alternative to antibiotics, promoting intestinal health without the adverse effects of antibiotics. The interaction between amoxicillin and tannins in the intestinal microbiota is complex, and further research is needed to optimize conditions for using tannins as feed additives to improve animal health and productivity.